Correspondence: Seán T. Ó Ceallaigh (1948)
Correspondence while President-Elect and while serving two terms as President.
Letter from Rev. D.F. Falvey, and copy of letter sent to him, relating to Mr. McGarrity’s donation of books to the Villanova College Library; from J. C. Walsh writing about James O’Mara and copy of reply sent; postcard from F. [Auleon] with general news (some is in French); and copies of letters sent to James A. Healy regarding the American Presidential elections and the projected abolition of the External Relations Act of 1936 and to James McGurrin complimenting him on his book on Bourke Cockran.